The Reynolds number effects and numerical modelling of microburst-like wind and the wind drag acting on staggered arrays - Sim, Tze Siang (2017)
The present study investigates the Reynolds numbers effects of the microburst-like wind, the numerical scheme necessary for modelling the flow as well as the wind drag force acting on staggered arrays of blocks near the surface using Computational Fluids Dynamics techniques. To authors' knowledge, these aspects of the microburst-like wind characteristics have never been studied elsewhere. Steady RANS is employed in the present study. The results of the Reynolds number effects is consistent with published experimental study. The Total DIminishing Variation (TDV) scheme for the convection term yield the best results for modelling impinging jet which is used to emulate microburst-like near-surface wind. The drag force is affected by the plan and frontal area index of the staggered array and pressure drag contributed the most to the total drag acting on the staggered arrays.